Inactivation of the waterborne marine pathogen Vibrio alginolyticus by photo-chemical processes driven by UV-A, UV-B, or UV-C LED combined with H2O2 or HSO5−. (1st April 2023) - Moreno-Andrés, Javier; Tierno-Galán, Miguel; Romero-Martínez, Leonardo; Acevedo-Merino, Asunción; Nebot, Enrique
Highlights: UV/HSO5 − showed higher inactivation rates compared to UV/H2 O2 . Regrowth was avoided only with UV/H2 O2 processes. Synergy among photochemical processes is more evident at longer wavelengths. Intracellular processes may gain importance in UV/H2 O2 treatment rather than extracellular ones. Abstract: Ultraviolet (UV) radiation is a well-implemented process for water disinfection. The development of emergent UV sources, such as light-emitting diodes (LEDs), has afforded new possibilities for advanced oxidation processes. The emission wavelength is considered to be an important factor for photo-chemical processes in terms of both biological damage and energetic efficiency, as the inactivation mechanisms and mode-of-action may differ according to the wavelength that is applied. In addition, these processes merit exploration for inactivating emerging pathogens, such as marine vibrios, that are important bacteria to control in maritime activities. The main goal of this study was to compare the disinfection efficacy of several UV-LED driven processes with different modes of action. First, the effect of UV-LEDs was assessed at different UV ranges (UV-A, UV-B, or UV-C). Second, the possible enhancement of a combination with hydrogen peroxide (H2 O2 ) or peroxymonosulfate salt (HSO5 − ) was investigated under two different application strategies, i.e. simultaneous or sequential. The results obtained indicate a high sensitivity of Vibrio alginolyticus to UV radiation, especially under UV-B (kobs  = 0.24 cm 2 /mJ) and UV-C (kobs  = 1.47 cm 2 /mJ) irradiation. The highest inactivation rate constants were obtained for UV/HSO5 − (kobs (cm 2 /mJ)=0.0007 (UV-A); 0.39 (UV-B); 1.79 (UV-C)) with respect to UV/H2 O2 (kobs (cm 2 /mJ)=0.0006 (UV-A); 0.26 (UV-B); and 1.54 (UV-C)) processes, however, regrowth was avoided only with UV/H2 O2 . Additionally, the disinfection enhancement caused by a chemical addition was more evident in the order UV-A > UV-B > UV-C. By applying H2 O2 (10 mg/L) or HSO5 − (2.5 mg/L) in a sequential mode before the UV, negligible effects were obtained in comparison with the simultaneous application. Finally, promising electrical energy per order (EEO ) values were obtained as follows: UV/HSO5 − (EEO (kWh/m 3 )=1.68 (UV-A); 0.20 (UV-B); 0.04 (UV-C)) and UV/H2 O2 (EEO (kWh/m 3 )=2.15 (UV-A); 0.32 (UV-B); 0.04 (UV-C)), demonstrating the potential of UV-LEDs for disinfection in particular activities such as the aquaculture industry or maritime transport. Graphical abstract: Image, graphical abstract